Translation and adaptation of software for the identification of maltreatment in children and adolescents - Zanatta Calza, Tiago; Castellá Sarriera, Jorge (Psicoperspectivas, 2015)
The aim of this work was to translate and adapt to the Brazilian context the content of the software Supporting Tool for Social Risk Management in Childhood and Adolescence. This software aims to help professionals to identify and proceed when facing cases that involve suspicion of child and adolescent abuse. The first study concerns the translation and adaptation of the software’s items. Judges were invited to evaluate the items individually, and the ones that did not reach 80% or more of agreement were discussed in a discussion group. 40 of the 290 items were discussed in the discussion group, which also suggested conceptual changes in accord to the Brazilian legislation. The group also suggested activating several protection services for each level of severity detected. The second study was the pilot application of the software with sixteen participants. Difficulties to understand certain words were pointed, as the ambiguity of some items. We discuss the importance of the software for notifying suspicion, as well as the development of tools for protecting children and adolescents.